Effectiveness of Social Media in Waqf Fundraising: A Case Study of Residential Land Waqf - Dodik Siswantoro; Mariati Aprilia Harahap (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2025)
Abstract: The objective of this paper is to assess the effectiveness of socialmedia-based fundraising as advertisement for a land waqf fund within aresidential complex. This study employs the qualitative data study usingsocial media platforms Instagram, Facebook, Kitabisa.com, SEO, Tiktok,and YouTube collected between 2020 and 2025 to analyze reach,engagement, and donation conversion, complemented by archivalfundraising records. The results indicate that social media advertising is noteffective, as few people are interested in contributing waqf funds throughthis method. This may be attributed to the fact that the term "waqffund for complex & quot; is not widely recognized, making it unsuitablefor this type of advertisement.